Optimization of a molecular technique for the characterization of bacterial and fungal soil communities in tropical ecosystems in southern Ecuador [Puesta a punto de una técnica molecular para el estudio de hongos y bacterias totales de suelo en ecosistemas tropicales del sur de Ecuador] - Cueva Agila, A. (2016)
A protocol for molecular characterization of soil microbial communities of tropical ecosystems (Tropical Dry Forest, TDF; Tropical Dry Scrub, TDS and Tropical Montane Forest, TMF) in southern Ecuador, was optimized. These ecosystems were selected due to their great biological interest, its high biodiversity and its vulnerability. Total genomic DNA from soil samples was isolated and then a polymerase chain reaction (PCR) was performed in order to amplify conserved regions of fungal and bacterial genome (using universal primers; ITS F-1-5.8S, EUB338-EUB 518; fungal and bacteria; respectively). We evaluated the effect of some parameters to reach the maximum efficiency of PCR. The results suggest that the DNA starting concentration was the variable with the highest impact on the reaction efficiency. We therefore identified the optimal dilutions per soil type: 1: 2, 1: 5, 1: 20 of the starting DNA preparation for TDS, TDF, and TMF respectively. Furthermore, the efficiency was increased when we determined the optimal concentration of MgCl2 and optimal annealing temperature for every soil type. The obtained average DNA concentration varies between ecosystems, being higher in the samples from TMF. This reflects the presence of higher microbial biomass in soils of this ecosystem compared to TDF and TDS. We, conclude that extrapolating parameters from one soil type to another which affect the PCR efficiency may result in errors. Our results suggest that it is necessary to standardize various parameters, taking into account the soil type and the conserved region of the genome to be amplified. Besides, we could verify that DNA concentration could be a consistent variable to estimate or compare the microbial biomass in different soil types. © 2016, Asociacion Argentina de la Ciencia del Suelo. All rights reserved.